2017
DOI: 10.1007/s40618-017-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin and insulin resistance: effect modification by age and 11 β-HSD2 activity in a population-based study

Abstract: Our data suggest that age and apparent 11β-HSD2 activity modulate the association of copeptin with insulin resistance at the population level but not MeTS or diabetes. Further research is needed to corroborate these results and to understand the mechanisms underlying these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(63 reference statements)
1
13
2
Order By: Relevance
“…Nevertheless, other studies have found associations between copeptin and the metabolic factors related to IR in children and adolescents [18][19][20], but the associations found have overall been less consistent compared with the studies in adults [2][3][4][5][6][7][8]. We have no obvious explanation for this age-related discrepancy, but it is important in this connection that the well described negative association between insulin and IR and the natriuretic peptide system could not be found among our adolescents, either [39], and that others have also found that age modulates the association of copeptin with IR [40]. Accordingly, in a family-based crosssectional study, the association between copeptin and IR could only be found among the middle-aged and elderly but not among the younger adults [40].…”
Section: Adolescents Versus Young Adultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, other studies have found associations between copeptin and the metabolic factors related to IR in children and adolescents [18][19][20], but the associations found have overall been less consistent compared with the studies in adults [2][3][4][5][6][7][8]. We have no obvious explanation for this age-related discrepancy, but it is important in this connection that the well described negative association between insulin and IR and the natriuretic peptide system could not be found among our adolescents, either [39], and that others have also found that age modulates the association of copeptin with IR [40]. Accordingly, in a family-based crosssectional study, the association between copeptin and IR could only be found among the middle-aged and elderly but not among the younger adults [40].…”
Section: Adolescents Versus Young Adultscontrasting
confidence: 68%
“…We have no obvious explanation for this age-related discrepancy, but it is important in this connection that the well described negative association between insulin and IR and the natriuretic peptide system could not be found among our adolescents, either [39], and that others have also found that age modulates the association of copeptin with IR [40]. Accordingly, in a family-based crosssectional study, the association between copeptin and IR could only be found among the middle-aged and elderly but not among the younger adults [40]. We speculated that metabolic dysfunction could take some time to develop.…”
Section: Adolescents Versus Young Adultscontrasting
confidence: 62%
“…Elevated glucocorticoid level in blood is clinically characterized by the development of diabetes, insulin resistance and visceral adiposity. 20 ROC curve analysis in the present study revealed that copeptin could be an excellent undependable predictor of DM risk with a sensitivity of 90.0% and specificity of 66.7% (AUC; 0.841) compared to fasting blood glucose and HbA1c (AUC; 0.872 and 0.803, respectively). These results were in line with Zhu et al 15 Moreover, copeptin shows high sensitivity and specificity (90.0% and 73.3%, respectively) (AUC; 0.921) for diagnosis of nephropathic complications of type II DM.…”
Section: Discussionmentioning
confidence: 49%
“…However, our results should be interpreted in the context of risk-benefit considerations. Several of the previous approaches to improve insulin sensitivity involved the use of various medications (10,19,31) , which are not free from inadvertent side effects (9,32,33) . Although lifestyle modification with exercise is a must for people with diabetes, it is very difficult to achieve and maintain (34) .…”
Section: Discussionmentioning
confidence: 99%
“…AVP has also been shown to stimulate cortisol release through activation of the hypothalamus-pituitary-adrenal (H-P-A) axis, via V1b receptor expressed in the anterior pituitary, thus further influencing glucoregulatory mechanisms (5,6) . This unfamiliar role of AVP in glucose metabolism has been recently supported in several clinical studies showing that increased copeptin, the C-terminal part of the AVP precursor peptide (8) , used as a surrogate marker of AVP, was associated with increased risk of insulin resistance (IR) (9)(10)(11) , the metabolic syndrome (12)(13)(14) and diabetes (6,9,(15)(16)(17)(18) .…”
mentioning
confidence: 99%